Adsorption of Fe(III) Ion in Tablets Fe Supplement by Black Tea Dregs and its Application in Inorganic Chemistry Learning - Yuli Nurmayanti; Detris Poba; Meida E. Marpaung (Jurnal Akademika Kimia, 2022)
The study of the adsorption of Fe(III) ion in Fe supplement by black tea dregs has been done. This study aims to investigate: (a) the Adsorption ability of Fe(III) ion in Fe supplement by black tea dregs (b) the Analysis result of Fe(III) amounts in a sample of Fe supplement when using black tea dregs. Several parameters were analyzed, such as; water and ash contents of the adsorbent, the optimum time, and the concentration of ion Fe(III) with tea dregs in a buffer medium (pH 4,8). The analysis of sample solution concentration of Fe(III) in this study using Genesys spectrophotometry at 590 nm. The result showed that the water and ash contents were 3.03 % and 0.9 %, respectively. Small percentages indicate that the adsorbent has met the standard (SNI) 06–3730-1995. The time and concentration optimum adsorption of Fe(III)-tea dregs were 60 minutes and 100 mg/L, respectively. The result of the adsorption ability of Fe(III) ion in Fe supplement by tea dregs was 70.4% with the adsorption concentration of ion Fe(III) were 7.07 mg/L. The research results obtained can be used as teaching materials for inorganic chemistry learning, and as a reference for new materials in the field of coordination chemistry and materials.